The Emerging Role of NETs in Venous Thrombosis and Immunothrombosis - Kimball, Andrew S.; Obi, Andrea T.; Diaz, Jose A.; Henke, Peter K. (Frontiers in Immunology, 2016)
Venous thrombosis (VT), a leading cause of morbidity and mortality worldwide, has recently been linked to neutrophil activation and release of neutrophil extracellular traps (NETs) via a processed called NETosis. The use of various in vivo thrombosis models and genetically modified mice has more precisely defined the exact role of NETosis in the pathogenesis of VT. Translational large animal VT models and human studies have confirmed the presence of NETs in pathologic VT. Activation of neutrophils, with subsequent NETosis, has also been linked to acute infection. This innate immune response, while effective for bacterial clearance from the host by formation of an intravascular bactericidal “net”, also triggers thrombosis. Intravascular thrombosis related to such innate immune mechanisms has been coined immunothrombosis. Dysregulated immunothrombosis has been proposed as a mechanism of pathologic micro-and macro-vascular thrombosis in sepsis and autoimmune disease. In this focused review we will address the dual role of NETs in the pathogenesis of venous thrombosis and immunothrombosis.